Risk Factors and Mortality Associated With Resistance to First-Line Antiretroviral Therapy: Multicentric Cross-sectional and Longitudinal Analyses. (15th April 2015) - Pinoges, Loretxu; Schramm, Birgit; Poulet, Elisabeth; Balkan, Suna; Szumilin, Elisabeth; Ferreyra, Cecilia; Pujades-Rodríguez, Mar
Abstract : Background: Understanding the factors associated with HIV drug resistance development and subsequent mortality is important to improve clinical patient management. Methods: Analysis of individual electronic health records from 4 HIV programs in Malawi, Kenya, Uganda, and Cambodia, linked to data from 5 cross-sectional virological studies conducted among patients receiving first-line antiretroviral therapy (ART) for ≥6 months. Adjusted logistic and Cox-regression models were used to identify risk factors for drug resistance and subsequent mortality. Results: A total of 2257 patients (62% women) were included. At ART initiation, median CD4 cell count was 100 cells per microliter (interquartile range, 40–165). A median of 25.1 months after therapy start, 18% of patients had ≥400 and 12.4% ≥1000 HIV RNA copies per milliliter. Of 180 patients with drug resistance data, 83.9% had major resistance(s) to nucleoside or nonnucleoside reverse transcriptase inhibitors, and 74.4% dual resistance. Resistance to nevirapine, lamivudine, and efavirenz was common, and 6% had etravirine cross-resistance. Risk factors for resistance were young age (<35 years), low CD4 cell count (<200 cells/μL), and poor treatment adherence. During 4978 person-years of follow-up after virological testing (median = 31.8 months), 57 deaths occurred [rate = 1.14/100 person-years; 95% confidence interval (CI): 0.88 to 1.48]. Mortality was higher in patients with resistance (hazard ratio = 2.08; 95% CI: 1.07 to 4.07 vs. <400 copies/mL), and older age (hazard ratio = 2.41; 95% CI: 1.24 to 4.71 for ≥43 vs. ⩽34 years), and lower in those receiving ART for >30 months. Conclusions: Our findings underline the importance of optimal treatment adherence and adequate virological response monitoring and emphasize the need for resistance surveillance initiatives even in HIV programs achieving high virological suppression rates. Abstract : Supplemental Digital Content is Available in the Text.